2019
DOI: 10.1039/c9ra06238f
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of oil from wet Antarctic krill (Euphausia superba) using a subcritical dimethyl ether method

Abstract: In this study, a novel method for obtaining high-quality krill oil from wet Antarctic krill by using subcritical dimethyl ether (SDE) was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Antarctic krill is one of the most abundant biomass species in Southern Ocean, which is estimated at about 500 million metric tons [1] . Whole Antarctic krill contains 11.9–15.4% protein, 3% ash, 2% carbohydrates, 0.5–3.6% lipid and 77.9–83.1% water [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Antarctic krill is one of the most abundant biomass species in Southern Ocean, which is estimated at about 500 million metric tons [1] . Whole Antarctic krill contains 11.9–15.4% protein, 3% ash, 2% carbohydrates, 0.5–3.6% lipid and 77.9–83.1% water [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have shown that liquefied DME can extract a variety of functional substances, such as astaxanthin [50,51], fucoxanthin [52], lutein [29,53], resveratrol and its glycosides [54], catechins and caffeine [55], tocopherol [56], gingerols and capsaicin [27]. Among these substances, carotenoids, such as astaxanthin, fucoxanthin and lutein, are hydrophobic, therefore difficult to encapsulate into liposomes by mechanical methods.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, n‐3‐PUFAs‐integrated PLs are more proficiently incorporated and absorbed into cell membranes than triglycerides (TAGs) [11, 12]. The efficient incorporation of KO into the cell membrane makes it a better choice than fish oil [12]. The EPA and DHA are omega‐3 polyunsaturated fatty acids which are the important component of the human cerebral cortex, skin, and brain [13–15].…”
Section: Introductionmentioning
confidence: 99%
“…These diverse lipids classes are mainly characterized by phospholipids (PLs) integrated with docosahexaenoic acid (DHA, C22:6, n‐3) and eicosapentaenoic acid (EPA, C20:5, n‐3) [1, 3]. As reported previously, n‐3‐PUFAs‐integrated PLs are more proficiently incorporated and absorbed into cell membranes than triglycerides (TAGs) [11, 12]. The efficient incorporation of KO into the cell membrane makes it a better choice than fish oil [12].…”
Section: Introductionmentioning
confidence: 99%